General Model of the Psychic Being within a Transformative Theory of Rationality - Lutz Goetzmann (EJP import test, 2022)
Summary: This paper presents a model of psychological relationships within the framework of transformative rationality, as being embedded in Hegel’s philosophy of mind. It is based on Laplanche’s fundamental anthropological situation with the enigmatic message of the Other, and the translation of these contents from the enclaved unconscious into the conscious mind, including the repression of unbearable contents in the repressed unconscious. The precision of this model is increased in various ways: The translation is represented more precisely with the tools of Bion’s transformation theory; and, the enclaved unconscious is determined by the Lacanian register of the Real, especially with the position of the thing and object a. The entire model is built around the concepts of matter and idea, real sensation and phenomenal thought, as well as the Imaginary and Symbolic. The embedding of the transformativity of the mind in Hegel’s philosophy shows that the psychoanalytic idea of ​​translation can be supplemented by Hegel’s idea of sublation. Thus, an increased capacity to transform what is not represented leads to a transformation of the personality in the sense of personal growth.
Keywords: New Phenomenology; Psychic Being; Real Unconscious; sensation; transformation